Use of Octogenarian Donors for Liver Transplantation: A Survival Analysis. Issue 9 (6th August 2014) - Ghinolfi, D.; Marti, J.; De Simone, P.; Lai, Q.; Pezzati, D.; Coletti, L.; Tartaglia, D.; Catalano, G.; Tincani, G.; Carrai, P.; Campani, D.; Miccoli, M.; et al.
<x xml:space="preserve">Abstract</x> Use of very old donors in liver transplantation (LT) is controversial because advanced donor age is associated with a higher risk for graft dysfunction and worse long‐term results, especially for hepatitis C virus (HCV)‐positive recipients. This was a retrospective, single‐center review of primary, ABO‐compatible LT performed between 2001 and 2010. Recipients were stratified in four groups based on donor age (<60 years; 60–69 years; 70–79 years and ≥80 years) and their outcomes were compared. A total of 842 patients were included: 348 (41.3%) with donors <60 years; 176 (20.9%) with donors 60–69 years; 233 (27.7%) with donors 70–79 years and 85 (10.1%) with donors ≥80 years. There was no difference across groups in terms of early (≤30 days) graft loss, and graft survival at 1 and 5 years was 90.5% and 78.6% for grafts <60 years; 88.6% and 81.3% for grafts 60–69 years; 87.6% and 75.1% for grafts 70–79 years and 84.7% and 77.1% for grafts ≥80 years (p = 0.065). In the group ≥80 years, the 5‐year graft survival was lower for HCV‐positive versus HCV‐negative recipients (62.4% vs. 85.6%, p = 0.034). Based on our experience, grafts from donors ≥80 years may provide favorable results but require appropriate selection and allocation policies.